Innovative culture of a teacher of a teaching of higher education: theoretical-methodological and empirical aspects - Serhii Bieliaiev; Ivan Stepanets (Scientific notes of the pedagogical department, 2023)
The article is devoted to the consideration of the problem of formation of innovative culture ofa teacher of a pedagogical institution of higher education. the innovative culture of the teacher is consideredas a scientific phenomenon, as well as a component of professionalism and a factor in improving theeducational process.The purpose of the article is to summarize the results of theoretical research into the essence ofinnovative culture, the relationship between this phenomenon and the concepts of innovative pedagogicalactivity, components of professional pedagogical activity and their formation in the process of professionaltraining in the conditions of a pedagogical institution of higher education.The logical relationship between the realization of material and spiritual culture in the innovativeactivity of an individual is presented. The peculiarity of the formation of an innovative culture in theprocess of professional pedagogical activity in the conditions of an innovative educational environmentis illustrated.The essence of the innovative culture phenomenon is revealed on the basis of axiological andstructural-functional approaches and its components are determined.The main factors that determine the formation of the need for the innovative orientation of theteacher’s pedagogical activity in the modern conditions of educational activity in the institution of highereducation are revealed.Evaluation criteria were formulated and an empirical study was carried out to determine the levels offormation of innovative culture among teachers of a pedagogical institution of higher education, and thecharacteristics of individual groups of teachers according to the determined levels were presented.Based on the analysis of the pedagogical characteristics of certain groups of scientific and pedagogicalworkers, the peculiarities of their atitude to perception, understanding, creation and application ofinnovations in the educational process were characterized: from active-positive to passive-negative.The key competencies of a modern teacher and their selection criteria are defined, which determinethe ability to engage in innovative pedagogical actvity and ensure the effective performance of pedagogicalfunctions and tasks in accordance with the content of the formed innovative culture.According to the results of the conducted research, the conclusions were made that the innovativeculture of the teacher is an integrated component of the professionalism of the pedagogical worker atthe personal and professional levels. The formation of the teacher’s innovative culture determines theeffectiveness and quality of pedagogical activity in the context of the development of the innovativeeducational environment of the institution of higher education.